Análisis hallazgos de auditoría financiera obtenidos en el cuestionario de control interno aplicado a la empresa Universitaria S.A. - Ajila Pineda, Adriana Cristina (My University, 2022)
The financial audit is the process of evaluating the financial statements of a company, in order to ensure the integrity and veracity of the accounting accounts, its implementation is essential to know the real economic and financial situation of the organization, in addition to allowing a good performance. In this case study there is evidence of a non-existent internal control and an inadequate organization of the company, which generates deficiencies in the organic and functional structure, since the employees do not have their functions defined. Therefore, the general objective of the research is to analyze the findings obtained during the execution of the financial audit of Empresa Universitaria S.A., through the application of an internal control questionnaire. For the fulfillment of this case study, a bibliographic methodology was implemented, for the use of indispensable theoretical foundations for the analysis of the present investigation, also the descriptive type of investigation was approached, for the compilation of necessary information in the description of the process carried out, with the purpose of providing a better understanding to the users of the financial statements, it was determined that the audit findings obtained through the application of an internal control questionnaire are of utmost importance for the detection of evident irregularities within the organization.
La auditoría financiera es el proceso de evaluación de los estados financieros de una empresa, con el fin de garantizar la integridad y veracidad de las cuentas contables, su implementación es fundamental para conocer la situación económica y financiera real de la organización, además de permitir un buen funcionamiento. En el presente caso práctico se evidencia un inexistente control interno y una inadecuada organización de la empresa, lo cual genera deficiencias en la estructura orgánica y funcional, dado que los empleados no tienen sus funciones definidas. Por lo tanto, el objetivo general de la investigación es analizar los hallazgos obtenidos durante la ejecución de la auditoría financiera a la Empresa Universitaria S.A, a través de la aplicación de un cuestionario de control interno. Para el cumplimiento de este caso práctico, se implementó una metodología bibliográfica, para la utilización de fundamentos teóricos indispensables para el análisis de la presente investigación, también se abordó el tipo de investigación descriptivo, para la recopilación de información necesaria en la descripción del proceso efectuado, con la finalidad de brindar un mejor entendimiento a los usuarios de los estados financieros, se determinó que los hallazgos de auditoría obtenidos a través de la aplicación de un cuestionario de control interno son de suma importancia para la detección de irregularidades evidentes dentro de la organización.
Keywords: AUDITORÍA; HALLAZGO; CONTROL INTERNO; CUESTIONARIO